Interleukin 3 stimulates proliferation via protein kinase C activation without increasing inositol lipid turnover. - Whetton, A D (1988)
Interleukin 3 (IL-3) is required for the survival and proliferation of the FDCP-Mix 1 multipotent stem cell line. IL-3 or phorbol esters can rapidly translocate protein kinase C from a cytosolic to a membrane-bound form in these cells. Phorbol esters were able to partially replace the requirement of FDCP-Mix 1 cells for IL-3. Down-modulation of protein kinase C levels by chronic treatment with phorbol ester markedly reduced the ability of the cells to proliferate in response to either IL-3 or phorbol esters. These data indicate that IL-3 can activate protein kinase C, leading to the survival and proliferation of stem cells. Protein kinase C is activated conventionally by complexing with diacylglycerol which accumulates in the cell membrane after agonist-stimulated hydrolysis of phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P2]. However, there was no detectable breakdown of PtdIns(4,5)P2 when IL-3 was added to FDCP-Mix 1 cells, nor was there detectable accumulation of inositol phosphates in response to IL-3. In contrast, rapid hydrolysis of PtdIns(4,5)P2 and accumulation of inositol 1,4,5-trisphosphate was elicited by readdition of horse serum to serum-starved cells, thus indicating that these cells possess the necessary machinery to undergo agonist-mediated inositol phospholipid breakdown. We conclude that the mechanism whereby IL-3 can activate protein kinase C leading to proliferation is not associated with inositol phospholipid hydrolysis.